Whom to Engage in Patient‐Engaged Research? Reflection on Selection. Issue 5 (11th October 2018) - Morain, Stephanie R.
Abstract: Engaging patients in research has come to be viewed as a vital component of high‐quality research, and funders now regard engaging patients and other stakeholders as a core criterion for funding decisions. In response, numerous empirical and conceptual papers have emerged to guide the process of engagement. However, as Emily Largent and colleagues rightly note, the inquiry of whom to engage has received less attention. While several teams have suggested that the selection of patients for engagement is an important consideration, researchers generally have little guidance on how to undertake this process. To that end, Largent and colleagues offer an important contribution to the literature. I agree with their argument regarding the centrality of critically examining which patients to engage in research and with their recommendations to maximize the positive goals of patient engagement. However, three issues warrant further consideration .